If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(v + -5) + 2v = 5 Reorder the terms: 3(-5 + v) + 2v = 5 (-5 * 3 + v * 3) + 2v = 5 (-15 + 3v) + 2v = 5 Combine like terms: 3v + 2v = 5v -15 + 5v = 5 Solving -15 + 5v = 5 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 5v = 5 + 15 Combine like terms: -15 + 15 = 0 0 + 5v = 5 + 15 5v = 5 + 15 Combine like terms: 5 + 15 = 20 5v = 20 Divide each side by '5'. v = 4 Simplifying v = 4
| 4(5x+4)+36=13x-4 | | 0.6t-00.2+0.1t=0.4 | | 14y^2+7x^3+49y=7 | | 1.2(p-0.2)=-1.4 | | 88-3x=24+5x | | p(x)=2x(x-4) | | -4+u=-9 | | -120.00+5.50x=182.50 | | 6a-3+a=11 | | 16=w/2+14 | | -42-15x=-9x | | -120.00+5.50=182.50 | | y^-3/y^8 | | (x)=x+4/3 | | 4x-12=3x+21 | | 27=t+26 | | 132=3x-4(7x+17) | | g^2-g=0 | | (x)=3x-4 | | 29=p-6 | | q^2-2q=0 | | 25=20+n | | 7(8)+4(-8)= | | .25y+3=-8 | | 14+z=29 | | q^2-5q-36=0 | | 7(8.4)+4(-8.3)=24 | | 5x+6(-8.3)=-8 | | 0.60x+0.05(12-x)=0.10(-38) | | p^2+8p-48=0 | | 5(3.4+-0.6y)+6y=-8 | | 5x^4-38x^2-16=0 |